READING MOTIVATION OF ENGLISH EDUCATION STUDY PROGRAM AT SECOND SEMESTER STUDENTS OF MERANGIN UNIVERSITY - Hartati, Hera; Oktawati, Herysa; Pratiwi, Anggia (Politeknik Negeri Bengkalis, 2024)
The purpose of this research was to describe about students’ motivation in reading at second semester of English Education Study Program in academic year 2023/2024. The reading motivation is needed by the students, because it is the reason or a motive why a student starts to reading. While, reading is an activity to get information as source of knowledge for students, it also can support them in doing their task in academic aspect and life in their future. This reasearch is descriptive quantitave research. It conducted in English Educational Program of Merangin University . The population is the second semester students consists of 28 students the sample of this reaserach is total sampling. The researcher used Motivation for Reading Questionnaire (MRQ) that filled by students as the instrument of collecting data. The instrument used four Likert scale, ranging from one to four, with scale of very different from me, a little different from me, a little like me, and a lot like me. In analyzing the data by connecting between the indicators of Motivation for Reading Questionnare consisted of 53 items, questionnaire is divided into three categories of competence and self-efficacy beliefs, goals for reading, and social purposes of reading. While the dimensions are self-efficacy, challenge, work avoidance, curiosity, involvement, importance, recognition, grades, competition, social, and compliance. it classified into high and low reading motivation. Based on calculating the data, the result shown that second semester students of English Education Study Program Merangin University had high reading motivation. It also shown that students had high category in reading compliance and low in work avoidance. The lecturer should use this instrument to know about students reading motivation before start to teach reading subject in the class. Therefore, she or he can design good ways to teach it.